Growth of the cereal market in Singapore. - Choy, Vanessa Wing Ki. (2008)
This is a project regarding the cereal market in Singapore – its present and future. As the existing cereal market is explored, we try to project a future direction for suppliers as well as retailers. This study explores the cereal market in Singapore from three different perspectives, namely the consumers, suppliers and retailers. The main issues discussed in the consumer survey are the breakfast habits, purchasing habits and consumers’ views regarding the future of the cereal market.